Exploring brain glutathione and peripheral blood markers in posttraumatic stress disorder: a combined [1H]MRS and peripheral blood study - Watling, Sarah E.; Rhind, Shawn G.; Warsh, Jerry; Green, Duncan; McCluskey, Tina; Tong, Junchao; Truong, Peter; Chavez, Sofia; Richardson, J. Don; Kish, Stephen J.; Boileau, Isabelle (Frontiers in Psychiatry, 2023)
Introduction: Oxidative stress has been implicated in psychiatric disorders, including posttraumatic stress disorder (PTSD). Currently, the status of glutathione (GSH), the brain’s most abundant antioxidant, in PTSD remains uncertain. Therefore, the current study investigated brain concentrations of GSH and peripheral concentrations of blood markers in individuals with PTSD versus Healthy Controls (HC). Methods: GSH spectra was acquired in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC) using MEGA-PRESS, a J-difference-editing acquisition method. Peripheral blood samples were analyzed for concentrations of metalloproteinase (MMP)-9, tissue inhibitors of MMP (TIMP)-1,2, and myeloperoxidase (MPO). Results: There was no difference in GSH between PTSD and HC in the ACC (n=30 PTSD, n=20 HC) or DLPFC (n=14 PTSD, n=18 HC). There were no PTSD group differences between peripheral blood markers (P>0.3) except for (non-significantly) lower TIMP-2 in PTSD. Additionally, TIMP-2 and GSH in the ACC were positively related in those with PTSD. Finally, MPO and MMP-9 were negatively associated with duration of PTSD. Conclusions: We do not report altered GSH concentrations in the ACC or DLPFC in PTSD, however, systemic MMPs and MPO might be implicated in central processes and progression of PTSD. Future research should investigate these relationships in larger sample sizes.